2011
DOI: 10.1007/s00436-011-2668-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of new commercial pediculicides against adults and eggs of Pediculus humanus capitis (head lice)

Abstract: The use of pyrethroids to control head louse infestations have suffered considerable loss of efficacy due to the development of resistance. In the last past years, several new alternative products to synthetic pyrethroids have been developed and are sold in the Argentinean market against head lice. The present study investigated the efficacy of two new Argentinean products Nopucid Qubit® and Nopucid Bio Citrus® and its comparison with two reference products Nyda® and Hedrin®. Nopucid Qubit® is a two-phase loti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…However, the addition of monoterpenes enhances the mortality of the formulations. The mortality of adults and eggs associated with the use of EOCs has been previously observed for similar under different experimental conditions and formulations (Toloza, Vassena & Picollo, 2008; Gonzalez-Audino et al, 2011; Gallardo & Mougabure-Cueto, 2012). …”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, the addition of monoterpenes enhances the mortality of the formulations. The mortality of adults and eggs associated with the use of EOCs has been previously observed for similar under different experimental conditions and formulations (Toloza, Vassena & Picollo, 2008; Gonzalez-Audino et al, 2011; Gallardo & Mougabure-Cueto, 2012). …”
Section: Discussionmentioning
confidence: 64%
“…The adulticidal and third-stage nymph activity was assessed using an ex vivo immersion test (Gallardo & Mougabure-Cueto, 2012). The ex vivo test consisted in the fully immersion of different batches of at least 10–15 lice deposited in a lid of a Petri dish (diameter 5.5 cm) during 5 min in 2 mL of the different prepared emulsions.…”
Section: Methodsmentioning
confidence: 99%
“…The assay was performed in respect of the manufacturer recommendations on a laboratory colony of body lice (P. humanus humanus) and their eggs. In other similar studies, the contact time in the assay differed from the contact time recommended by the manufacturer (Meinking et al 1986;Meinking et al 2001;Heukelbach et al 2008aHeukelbach et al , 2009Abdel-Ghaffar 2010;Gallardo et al 2012).…”
Section: Introductionmentioning
confidence: 89%
“…opposite to the scalp (Burkhart & Burkhart, 2005). Many studies have been reported about the disinfestation of head lice, as well as infection status surveys and the composition of the nit sheath (Hunter & Barker, 2003;Elston, 2005;Clark, 2009;Lee et al, 2009;Oh et al, 2010;Gallardo et al, 2012). However, studies on the morphological characteristics of eggs have been insufficient.…”
Section: Introductionmentioning
confidence: 99%